The Birth of East-Belgian Identity and the Treaty of Versailles. A Critical Legal Analysis - Vanhullebusch, Matthias (Nationalities Papers, 2025)
„In the former districts of Eupen and Malmedy, present-day East-Belgians, in particular academic and socio-political elites, draw their collective identity, amongst others, from the historical injustices inflicted upon them ever since the adoption of the Treaty of Versailles. The transfer of sovereignty from Germany to Belgium was then the subject of a popular consultation organised by the transitional Belgian authorities in those territories. Favouring national over popular sovereignty, those authorities de facto undermined the freedom of choice and imposed their annexation to Belgium which the League of Nations, despite criticisms, consecutively endorsed. Much has been said about this petite farce belge yet not from a legal point of view. Thus, this article sheds a different light on the historical accounts of those events which are instrumentalised to construct the contemporary collective identity of the German-speaking Community of Belgium.“
Keywords: Identität; Nationalismus; Versailler Vertrag (1919)

Die Bedingungsklausel für Eupen-Malmedy im Versailler Vertrag - Jousten, Wilfried (Zwischen Venn und Schneifel, 2021)
Keywords: Annexion; Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

"New Belgians" living in an ancient Belgian soil? The annexation and integration of the East Cantons - Brüll, Christoph (Beyond the Great War. Belgium 1918–1928, 2018)
Keywords: Annexion; Staatsgrenze; Versailler Vertrag (1919)

Pierre Nothomb, het comité de politique nationale en de Belgische annexionistische campagne tijdens en na de Eerste Wereldoorlog - Waele, Maria de (Studies over De Sociaaleconomische Geschiedenis Van Limburg/Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2015)
Keywords: Annexion; Erster Weltkrieg; Nothomb, Pierre (1887–1966); Versailler Vertrag (1919)

Belgien und die Ostkantone im Versailler Vertrag. Irredenta-Gebiet, militärische Pufferzone oder Trostpreis? - Balace, Francis (Zoom 1920–2010. Nachbarschaften neun Jahrzehnte nach Versailles, 2012)
Keywords: Annexion; Eupen; Malmedy; Ostbelgien; Staatsgrenze; Versailler Vertrag (1919)

Zoom 1920–2010. Nachbarschaften neun Jahrzehnte nach Versailles - Brüll, Christoph (Grenzecho-Verlag, 2012)
Aus den Verlagsangaben: „Am 20. September 1920 wurde das Gebiet von Eupen und Malmedy auf der Grundlage des Versailler Vertrags belgisch. Das Jahr 1920 bildet somit die entscheidende Zäsur in der bewegten Geschichte dieses Grenzlandes im 20. Jahrhundert. Zum 90. Jahrestag der Gebietsübertragung leistete eine Tagung in St. Vith die historische Einordnung der Ereignisse und ihrer Folgen. Dieses Buch möchte durch das Teleobjektiv die großen Entwicklungslinien des Gebietes der heutigen Deutschsprachigen Gemeinschaft einfangen. Durch das Weitwinkelobjektiv wird diese Entwicklung in einen breiteren historischen und politischen Kontext eingeordnet. Dabei wird auch deutlich, dass die Geschichte nicht überall eine vergleichbare Wendung gefunden hat. Thematisiert werden jedoch nicht nur die damaligen Ereignisse, sondern auch der bis in die Gegenwart wirkende schwierige Umgang mit dieser Vergangenheit.“
Keywords: Eupen; Malmedy; Staatsgrenze; Versailler Vertrag (1919)

Dictating Democracy. The Impact of Governor Baltia’s Transitory Regime on Local Government in Eupen-Malmedy, 1919–1922 - O'Connell, Vincent (International Journal of Regional and Local Studies, 2011)
Keywords: Baltia, Herman (1863–1938); Eupen-Malmedy; Militärgouverneur; Versailler Vertrag (1919)

Eupen and Malmedy - George, Robert H. (Foreign Affairs, 1927)
Keywords: Eupen-Malmedy; Staatsgrenze; Versailler Vertrag (1919)

The Belgian-German Boundary Demarcation - A. R. H. (The Geographical Journal, 1921)
Keywords: Staatsgrenze; Versailler Vertrag (1919)

La Nationalité des Habitants des Cercles d’Eupen et de Malmédy d’Après le Traité de Paix de Versailles - Nisot, Joseph (Journal du Droit International, 1921)
Keywords: Annexion; Eupen-Malmedy; Staatsangehörigkeitsrecht; Staatsgrenze; Versailler Vertrag (1919)